1991
DOI: 10.1172/jci115304
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of [Ca2+]i, [Pi]i, and pHi to altered diastolic myocyte tone during partial metabolic inhibition.

Abstract: Ischemia may cause increased or decreased distensibility of the left ventricle, but the cellular mechanisms involved have not been clarified. We examined the possible contributions of changes in intracellular inorganic phosphate, pH, and Ca2" concentrations to altered diastolic function in cultured myocytes subjected to partial metabolic inhibition. Paced cultured embryonic chick and adult rabbit ventricular myocytes superfused with 20 mM 2-deoxyglucose (2DG) exhibited an increase in end-diastolic intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…To assure that the results obtained in isolated myocytes were representative of the behavior of the intact heart, the 2DG perfusion protocol described above in the isolated myocytes were repeated in isolated buffer-perfused hearts from additional aortic-banded rats 8-9 wk after banding (n = 7) and age-matched sham-operated controls (n = 7). The isovolumic buffer-perfused heart preparation has been described in detail previously (11,12,13). Left ventricular isovolumic balloon volume was adjusted to achieve a left ventricular end-diastolic pressure of 10 mmHg in both groups; at this level of diastolic pressure, balloon volume was comparable in the hypertrophy and control groups (0.19±0.01 vs. 0.21±0.02 ml, NS).…”
Section: Glycolytic Inhibition In Hypertrophied Myocytesmentioning
confidence: 99%
See 3 more Smart Citations
“…To assure that the results obtained in isolated myocytes were representative of the behavior of the intact heart, the 2DG perfusion protocol described above in the isolated myocytes were repeated in isolated buffer-perfused hearts from additional aortic-banded rats 8-9 wk after banding (n = 7) and age-matched sham-operated controls (n = 7). The isovolumic buffer-perfused heart preparation has been described in detail previously (11,12,13). Left ventricular isovolumic balloon volume was adjusted to achieve a left ventricular end-diastolic pressure of 10 mmHg in both groups; at this level of diastolic pressure, balloon volume was comparable in the hypertrophy and control groups (0.19±0.01 vs. 0.21±0.02 ml, NS).…”
Section: Glycolytic Inhibition In Hypertrophied Myocytesmentioning
confidence: 99%
“…There is evidence that glycolytic flux is closely linked with diastolic relaxation and transsarcolemmal ion flux, implicating a role in the restoration of resting cytosolic Ca2" levels (9, 10). Ikenouchi et al ( 11 ) demonstrated that glycolytic inhibition by 2-deoxyglucose (2DG) 1 causes impairment of myocyte relaxation in association with an increase in diastolic intracellular Ca2" in normal isolated cultured embryonic chick myocytes and paced adult rabbit ventricular myocytes under oxygenated conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such beneficial effects of glycolysis have been attributed to a preferential ability of glycolytically derived ATP to restore calcium homeostasis (20). Other lines ofevidence have also hinted at linkages between glycolytic inhibition and abnormal Ca2" homeostasis (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%